A creditable position James Carson Breckinridge and the development of the Marine Corps Schools - Elkins, Troy R. (Kansas State University, 2011)
Immediately after World War I, the Commandant of the United States Marine Corps implemented an officer education program. Called the Marine Corps Schools (MCS), the Commandant, Major General John A. Lejeune, gave the schools the mission of educating officers throughout their career. MCS struggled during its first decade of existence due to operational tempo and a poor curriculum. The direction of MCS changed greatly with the assignment of James Carson Breckinridge as the commanding officer in 1928. The purpose of this thesis is to examine the role Breckinridge, an unconventional and intellectual officer, played in reviving the MCS and turning it into the authority on Small Wars and Amphibious Operations. It will show that Breckinridge, drawing on observations made of college education systems, focused the Marine Corps Schools on the task of teaching officers to analyze problems and find solutions and not rely on memorized book answers.
Keywords: American history; Military history; United States Marine Corps; Professional military education; James Carson Breckinridge; Inter-war; History (0578)